Assessment of aflatoxin contamination in Bambara groundnut (Vigna subterranea L.) produced in Burkina Faso, West Africa - Amidou S. Ouili; Cheik Omar Tidiane Compaoré; Assiètta Ouattara; Djamilatou Dabré; Ynoussa Maiga; Mahamadi Nikiema; Mahama Ouedraogo; Aboubakar Sidiki Ouattara (Cogent Food & Agriculture)
Bambara groundnut is a key protein source in West Africa but may face mycotoxin contamination risks. In this study, 30 Bambara groundnut samples, potentially from different local cultivars, were collected during the dry season from three climatic zones of Burkina Faso (Sahelian, Sudano-Sahelian and Sudanian), with 10 samples collected from each zone. Samples were evaluated for aflatoxin contamination using Liquid Chromatography coupled with tandem Mass Spectrometry (LC-MS/MS). Aflatoxin B1 was detected in 50.00% of the samples, with concentrations ranging from 0.01 to 0.19 μg kg−1. Aflatoxin B2 was found in 73.33% of the samples at levels ranging from 0.03 to 0.23 μg kg−1. Aflatoxin G1 was found in only 16.33% of samples, with levels between 0.09 and 0.31 μg kg−1. Aflatoxin G2, on the other hand, was found in 67.00% of samples with concentrations ranging from 0.04 μg kg−1 to 0.27 μg kg−1. Overall, aflatoxin concentrations in Bambara groundnut grain are relatively low, but frequent consumptions of small concentration of aflatoxins leads to chronic health risk to consumers. Therefore, it is necessary to improve grains protection to prevent the production of toxigenic fungi and subsequent aflatoxin contamination in groundnut. These measures should be applied across all regions of Burkina Faso where Bambara groundnut is grown.